Molecular markers of breast cancer cells identified in fine needle aspiration samples from resected sentinel lymph nodes - Cannone, Maria; Oliveri, Claudio; Roz, Elena; Rispoli, Francesca; Ferrarese, Stefania; Alexiadis, Spyridon; Barberis, Massimo C P (Acta cytologica, 2006)
To analyze a procedure for breast cancer that requires performance of a molecular test before extensive intraoperative examination, fine needle aspiration cytology (FNAC) of surgically removed sentinel lymph nodes (SLNs). The diagnostic accuracy of extensive histologic examination and immunohistochemistry (IHC) of 101 SLNs from 98 breast carcinoma patients were compared with that of the evaluation of 2 specific mRNA markers by reverse transcriptase polymerase change reaction (mammaglobin and MUC-1). Cell specimens were obtained by FNAC of the SLNs immediately before freezing. Metastases were detected on frozen sections in 19 cases (18.81%). IHC on serial sections confirmed the metastases and showed micrometastases or isolated tumor cells in 24 SLNs (23.76%). Mammaglobin was expressed in 20 FNAC specimens (19.80%). MUC-1 assay was positive in 11 cases only (10.89%). This technique allows a complete histologic examination without sacrifice of part of the SLN and at the same time is a valuable diagnostic adjunct to the detection of occult tumor cells. Moreover, it is less expensive and time consuming than extensive IHC.